Analysis of the determinants of financial inclusion in Central and West Africa. Issue 4 (1st October 2016) - Soumaré, Issouf; Tchana Tchana, Fulbert; Kengne, Thierry Martial
Abstract: Using data from the Global Financial Inclusion database (Global Findex) of the World Bank, this study attempts to identify and analyse the determinants of financial inclusion in Central and West Africa, two of the least financial inclusive regions of the Africa continent. The findings indicate that access to formal finance in the two regions is mainly driven by individual characteristics such as gender, education, age, income, residence area, employment status, marital status, household size and degree of trust in financial institutions. However, Central Africa and West Africa differ with the entire Africa region on a number of important determinants of access to finance. Specifically, educated, working-age, urban resident and full-time employed are significant individual characteristics of access to formal account in both regions and in Africa. However, being male and/or married are positive determinants of financial inclusion for Central Africa and Africa, whereas income is significant in West Africa and Africa. In addition, household size has a negative impact on account ownership in West African and not in Central Africa. When we use the other financial inclusion indicators (saving, borrowing or frequency of use), the above determinants remain all significant for Africa, but not necessarily for Central Africa or West Africa, where they have different degree of significance. As policy recommendations, governments and their partners in these regions should adopt or strengthen regulatory laws to better protect financial services consumers, enlarge population access to education, ease access to finance for the vulnerable groups (women, youth, poor, etc.), and continue their effort to increase the number of permanent and stable jobs created with special focus on gender and marital status in Central Africa and income and household size in West Africa.